Resistance exercises as an important form of non-pharmacologic treatment of diabetes - Alzubedi, Adam; Kusz, Monika; Popiołek, Joanna (Journal of Education, Health and Sport, 2018)
Diabetes, which is a chronic, systemic disease, carries the risk of numerous complications. “An ounce of prevention is worth a pound of cure” - therefore it is important and cost effective to properly manage diabetes and prevent its complications, which can be achieved, among other things, by keeping proper glycemic control, taking care of the lipid profile and maintaining the recommended blood pressure values. In addition to pharmacologic treatment, non-pharmacologic treatment is also vital and often underestimated in practice. This type of treatment includes a healthy diet and physical activity. There are different types of physical activity, each of which has a different effect on metabolism. The aim of this article is to present resistance exercises in comparison with other models of physical effort recommended for the managing of diabetes. Resistance exercises can have a greater effect on the metabolic equilibrium of diabetes than aerobic exercises due to longer and more stable decreases in post-workout glycemia levels, and a similar effect on other aspects of health. Strength training can be an effective alternative to currently recommended aerobic exercises due to the small differences in contraindications and the significant benefits. In order to be able to compare both types of physical effort more accurately and to identify the model that has a greater effect on metabolism more clinical studies are needed.